Cumulative Effects of Labor Market Distortions in a Developing Country - Pehr-Johan Norbäck (The Research Institute of Industrial Economics (IUI), 1999)
This paper considers a small open economy with an input-output industrial structure that creates vertical linkages and multiple equilibria. An imperfect labor market is introduced by assuming unionized labor. It is shown that a deregulation of the labor market may trigger a large discontinuous expansion of industrial output, as reduced wage-costs start a circular, cumulative process in which expansions of the up-and downstream industries promote each other. Centralization of collective bargaining may, however, also be conductive to industrialization.
Keywords: F12; J50; O11; 330; Vertical linkages; Multiple equilibria; Labor unions; Gewerkschaftsmitgliedschaft; Unvollkommener Markt; Arbeitsmarkt; Interindustrielle Verflechtung; Kleine offene Volkswirtschaft; Theorie